A Method to Design Profiled Cutting Tools for Inner Turning - Dragoi, Mircea Viorel; Parv, Luminita; Mija, Adrian; Oancea, Gheorghe (Symmetry, 2022)
Designing the profile of cutting tools is a specific problem in manufacturing engineering. The profile of the cutting tool has a direct influence on the dimensional and shape precision of the machined parts. When it comes to cutting tools for internal turning, the problem of profile design becomes even more complex, because of the added restrictions the profile and the cutting tool itself are subjected to. Despite its importance and complexity, this problem has been rather poorly considered in the literature. Some side aspects, such as measuring the profile, its wear, and its influence on the part’s geometrical precision have been studied, but not the design process of the profiled shape of cutting edges. This research fills a gap in the literature. It considers profiled cutting tools, in general; and, in particular, investigates tilted cutting edges. The novelty of the present article lies in a method to determine the profile of cutting tools for turning inner-profiled surfaces. The method is CAD-based and provides accurate results. It considers the part’s inner profile, its inner diameter, and the tilting angle of the cutting edge. In addition, possible undercuts are taken into account. The method was validated using two relevant case studies. Despite profiled cutting tools having a certain drawback, which is emphasized in the article, this is balanced by the advantages that their use offers manufacturing.
Keywords: turning inner surfaces; profiled cutting tools; tilted cutting edge; special cutting tools design; undercut; cutting forces; symmetrical profile